The Potential and Challenges of Waqf in Overcoming Economic Crises and Recessions - Syamsul Bachri; Imron Rosyadi; Muthoifin (al-Afkar, Journal For Islamic Studies, 2024)
This research examines waqf's potential to revitalize economies during crisis-induced recessions. It presents an analysis of economists' theories on recession causes, addressing factors such as the separation between financial and real sectors and the influence of price speculation. The historical context of 20th and 21st-century economic recessions is explored, highlighting the consistent repercussions of reduced economic growth and activity. Additionally, the study delves into waqf's development across countries, revealing significant asset values yet limited productivity. We found various models of waqf development that offer avenues for progress, with potential economic benefits including increased economic activities, enhanced economic growth, price stability, improved production, reduced unemployment, and wealth disparity reduction. Despite this potential, we found that waqf's global impact remains limited due to inadequate administration, weak management, and a lack of government support. The research underscores the importance of effective waqf management and supportive policies to unlock its full potential and contribute to global economic stability.